The Role of Breast Cancer Survivors and Non-Survivors in Improving Breast Self-Examination (BSE) Behavior in Reproductive-Age Women - Rena Oki Alestari; Neneng Safitri (KHD Production, 2024)
Breast cancer is a cause of death, and the incidence rate increases by 5% every year. Breast cancer is a solid cancer. In Indonesia, breast cancer is the second most common cancer in women. This study aimed to analyze the role of breast cancer survivors and non-survivors to improve behavior about breast self-examination (BSE) in women of reproductive age in Palangka Raya City. The research design was a pretest posttest control group design, respondents were 78 women of childbearing age aged 20-30 years, who were randomly selected in Palangka Raya City. This study used a breast self-examination (BSE) skills assessment sheet questionnaire, modules and leaflets. Data were analyzed using the independent sample t-test. There is a significant difference in the increase in knowledge between counseling by survivors and non-survivors with ρ=0.000, increased attitude ρ=0.056, increased skills ρ=0.000. Survivor resource persons are better than non-survivor resource persons to improve knowledge, attitudes and skills about breast self-examination (BSE) in women of childbearing age.